The management philosophies and controls in capital budgeting : (a comparative study of South African subsidiaries of multi-national corporations) - Bishton, R. E.(Robert Edward) (Stellenbosch : Stellenbosch University, 2012)
Full text to be digitised and attached to bibliographic record.